2013
DOI: 10.1111/iju.12345
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal polyuria and decreased serum testosterone: Is there an association in men with lower urinary tract symptoms?

Abstract: Objectives:To investigate the putative association between nocturia and decreased serum testosterone in men with lower urinary tract symptoms. Methods: Frequency volume charts and serum testosterone levels of patients visiting the outpatient clinic for lower urinary tract symptoms were collected and analyzed. Age, prostate volume, body mass index and the presence of comorbidities were accounted for. Frequency volume charts were analyzed for pathophysiological components of nocturnal polyuria, global polyuria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 25 publications
(59 reference statements)
4
25
0
Order By: Relevance
“…Since T therapy results in a sustained and marked decrease in body weight, WC, and BMI [151], weight loss associated with T treatment may contribute to the observed improvement in LUTS. Our findings are also supported by a number of human and animal studies demonstrating a strong independent association between the components of Met S and BPH/LUTS as discussed above [153]. …”
Section: Does Testosterone Therapy Improves Lower Urinary Tract Symptsupporting
confidence: 89%
See 1 more Smart Citation
“…Since T therapy results in a sustained and marked decrease in body weight, WC, and BMI [151], weight loss associated with T treatment may contribute to the observed improvement in LUTS. Our findings are also supported by a number of human and animal studies demonstrating a strong independent association between the components of Met S and BPH/LUTS as discussed above [153]. …”
Section: Does Testosterone Therapy Improves Lower Urinary Tract Symptsupporting
confidence: 89%
“…Adjusted and unadjusted longitudinal models showed modest, positive effects of T therapy on LUTS, with 7.1% lower total IPSS over time (p=0.004) and 7.9% reduction of irritative scores (p<0.001) in T treated compared with untreated men, but no change in IPSS obstructive scores (p=0.33). Shigehara et al [143] found that at 6 months, T therapy with 250 mg of T enanthate every 4 weeks was associated with decreased nocturia, improved sleep conditions, and improved QoL, which in and of itself has been shown to improve endogenous T production [153]. T treatment has also been shown to improve voiding function, urinary symptoms and changes in bladder wall thickness observed with androgen deficiency [140141145].…”
Section: Does Testosterone Therapy Improves Lower Urinary Tract Symptmentioning
confidence: 99%
“…Many reports have investigated the relationship between testosterone and LUTS, whereas few have focused on the relationship between testosterone and nocturia in men [21222324252627]. Recent studies have suggested that testosterone has an ameliorative effect on nocturia (Table 1).…”
Section: Relationship Between Testosterone and Nocturiamentioning
confidence: 99%
“…Another study involving 2,180 patients demonstrated that testosterone decreased 0.142 ng/mL for every time the patients woke at night to urinate, and that nocturia, especially nocturnal polyuria, was associated with decreased serum testosterone [22]. Kim et al [23] suggested that serum total testosterone levels may have a beneficial effect on lower urinary tract function, and showed that they were significantly lower in patients with 4 or more episodes of nocturia per night.…”
Section: Relationship Between Testosterone and Nocturiamentioning
confidence: 99%
See 1 more Smart Citation